Manajemen Sistem Monitoring Pembayaran Hutang Pembelian Untuk Estimasi Pengeluaran Sebagai Pendukung Keputusan - Janu Ilham Saputro; Dedi Martono; Siti Sunariah (UNIVERSITAS RAHARJA, 2019)
The development of information technology has recently experienced such rapid development, this is followed by the development of information media that continues to grow. Companies are always required to follow this development in order to improve service quality and company performance. At present, various companies are required to pay taxes according to the rules that have been determined as a form of the company's obligation to the state. Problems that often occur in the company are uncontrolled po and tax invoices, so that often there is an overpayment of tax debt from what should be, and this causes delays in decision making, so that financial planning in payment of purchase debt. To be able to overcome this problem, a computerized system is needed to monitor the purchase debt calculation system as a decision support for expenditure estimation. To be able to realize this, it takes several design steps by analyzing the procedures that are running, building a system design with usecase diagrams, activity diagrams, squen diagrams and class diagram designs as a form of data storage center which can then be processed automatically so that it becomes the basis for decision making. Then implemented by building a web-based system that can be used in the company. The expected benefits are the creation of a system that is able to run effectively and efficiently, as well as being able to print reports quickly and accurately, so as to reduce problems that often occur in the company.